Alfalfa Cost-Return Budget in South Central and Southeast Kansas - Shoup, Douglas; O'Brien, Daniel M.; Ibendahl, Gregg (My University, 2015)
This publication contains information for a projected budged reflecting expected income and cost based on alfalfa production in south central and southeast Kansas.
MF363_2015_04
Keywords: MF363; Economics; Crops; MF